2018
DOI: 10.3389/fpsyg.2018.02279
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Emotional Well-Being in Older Breast Cancer Patients: Results From an eHealth Intervention

Abstract: Breast cancer is the most common cancer in women worldwide, with increases in diagnoses at all ages. Due to several age-related factors, older breast cancer patients show particular difficulties in adjusting to breast cancer and its related treatments. One consistent indicator of vulnerability to long-term complications is emotional distress occurring within 3 months of diagnosis. Thus, it is critical to develop early interventions specifically aimed at mitigating distress and promoting emotional wellbeing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 74 publications
(82 reference statements)
1
34
0
1
Order By: Relevance
“…Frequency of internet use was also the predictive variable with p -value< 0.05 where chronic patients those who use internet on a daily basis are almost 3 (AOR: 2.96) times more likely to have high eHealth literacy skill when compared to those who use internet 1 day and less than 1 day a week with 95%CI: (1.08, 6.76). This finding is similar with different studies confirming that frequent internet users possess higher eHealth literacy skill [ 15 , 30 , 57 , 58 ]. In addition, higher computer literacy was also highly associated with higher eHealth literacy skill which is similar with studies done elsewhere [ 59 – 61 ].…”
Section: Discussionsupporting
confidence: 92%
“…Frequency of internet use was also the predictive variable with p -value< 0.05 where chronic patients those who use internet on a daily basis are almost 3 (AOR: 2.96) times more likely to have high eHealth literacy skill when compared to those who use internet 1 day and less than 1 day a week with 95%CI: (1.08, 6.76). This finding is similar with different studies confirming that frequent internet users possess higher eHealth literacy skill [ 15 , 30 , 57 , 58 ]. In addition, higher computer literacy was also highly associated with higher eHealth literacy skill which is similar with studies done elsewhere [ 59 – 61 ].…”
Section: Discussionsupporting
confidence: 92%
“…The specific intervention described for geriatric cancer patients are coping and communication support for older cancer patients (CCS) and CARE intervention—cancer and aging: reflections of elders [ 24 ]. Also, web-based intervention (e-health) resulted in significant support for elderly BC patients during their upcoming chemotherapy and offered them effective coping strategies [ 25 ].…”
Section: Distress Anxiety and Depressionmentioning
confidence: 99%
“…22 Villani et al evaluated eHealth stress inoculation training intervention on emotional regulation and cancer-related well-being in 29 women over 55 years of age with breast cancer (mean age, 62.76 years), and revealed a good level of acceptance of the eHealth intervention, an increase in relaxation and a reduction in anxiety among women in the intervention group. 23 Hoogland et al surveyed eHealth literacy in older adults with cancer and found that older adults had significantly lower eHealth literacy than younger patients, which suggests older cancer patients' needs and abilities should be considered when designing and implementing health information technology. 17 There is a need for comprehensive evidence to inform the research and development of digital health solutions, and to understand the imperatives of designing, implementing and evaluating digital healthcare initiatives in the context of geriatric oncology populations.…”
Section: Open Accessmentioning
confidence: 99%